Micro-scale continuous and discrete numerical models for nonlinear analysis of masonry shear walls. (15th September 2017) - Petracca, Massimo; Pelà, Luca; Rossi, Riccardo; Zaghi, Stefano; Camata, Guido; Spacone, Enrico
Highlights: A novel damage continuous micro-model for masonry shear walls is presented. A novel bi-dissipative damage model able to represent dilatancy of mortar joints. The proposed micro-model is validated and compared to others available in literature. Results are critically discussed and compared. Abstract: A novel damage mechanics-based continuous micro-model for the analysis of masonry-walls is presented and compared with other two well-known discrete micro-models. The discrete micro-models discretize masonry micro-structure with nonlinear interfaces for mortar-joints, and continuum elements for units. The proposed continuous micro-model discretizes both units and mortar-joints with continuum elements, making use of a tension/compression damage model, here refined to properly reproduce the nonlinear response under shear and to control the dilatancy. The three investigated models are validated against experimental results. They all prove to be similarly effective, with the proposed model being less time-consuming, due to the efficient format of the damage model. Critical issues for these types of micro-models are analysed carefully, such as the accuracy in predicting the failure load and collapse mechanism, the computational efficiency and the level of approximation given by a 2D plane-stress assumption.